2020
DOI: 10.1021/acs.jafc.0c02949
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Escherichia coli for de Novo Production of Betaxanthins

Abstract: Betalains are emerging natural pigments with high tinctorial strength and stability, physiological activities, and fluorescent properties for potential application in food, cosmetic, and pharmaceutical industries. Betalains including yellow betaxanthins and red betacyanins are mainly restricted in the Caryophyllales plants. To expand the availability of individual betaxanthins, here, we constructed an Escherichia coli BTA6 for de novo biosynthesis of betalamic acid. Using this strain as a monoculture platform,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…After resveratrol was efficiently produced from p-coumaric acid, we further extended the resveratrol biosynthesis from glucose. For producing p-coumaric acid from glucose, we used our previously reported l -tyrosine overproducing strain BAK11(DE3) [ 26 ] as chassis. For screening the expression pattern compatible with chassis, the PcTAL gene from Phanerochaete chrysosporium [ 27 ] under the control of the trc promoter was cloned into various copy number plasmids pACYCDuet-1, pCDFDuet-1, and pETDuet-1, and transformed into strain BAK11(DE3) to generate strains BCR1, BCR2, and BCR3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After resveratrol was efficiently produced from p-coumaric acid, we further extended the resveratrol biosynthesis from glucose. For producing p-coumaric acid from glucose, we used our previously reported l -tyrosine overproducing strain BAK11(DE3) [ 26 ] as chassis. For screening the expression pattern compatible with chassis, the PcTAL gene from Phanerochaete chrysosporium [ 27 ] under the control of the trc promoter was cloned into various copy number plasmids pACYCDuet-1, pCDFDuet-1, and pETDuet-1, and transformed into strain BAK11(DE3) to generate strains BCR1, BCR2, and BCR3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the intracellular availability of malonyl-CoA, we applied the RppA biosensor [ 25 ] for screening CRISPRi inhibitory targets. The upstream strain was constructed from arabinose-deficient and l -tyrosine-overproducer [ 26 ] by introducing the PcTAL gene [ 27 ]. To stabilize the subpopulation in coculture system, we designed and constructed a resveratrol addiction circuit in the upstream strain that coupled its growth with the resveratrol production of the downstream strain.…”
Section: Introductionmentioning
confidence: 99%
“…For the de novo biosynthesis of kaempferide, we chose the PcTAL gene from Phanerochaete chrysosporium 42 as the upstream module and tyrosine overproducing strain BAK11-(DE3) as the chassis host, which was constructed previously in our lab. 44 PcTAL and At4CL were coexpressed in pCDFduet-1 and transformed with pESI1 and pEOM9 into BAK11(DE3). As shown in Figure 5, the resulting strain BANS2 produced a small amount of kaempferide (1.6 ± 0.1 mg/L) with growth arrest, while the accumulation of p-coumaric acid was massive (773.2 ± 23.2 mg/L).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The production of betalains has also been transferred to microbes by metabolic engineering. Various betaxanthins and betacyanins have been produced in E. coli, with yields of up to 288 mg per L (Guerrero-Rubio et al, 2019;Hou et al, 2020). Grewal et al (2018) reported the production of betalains in the yeast S. cerevisiae, achieving a titer of 17 µg per mL for betanin, the most industrially relevant betalain.…”
Section: Discussionmentioning
confidence: 99%